Steg Analysis Algorithm for Edge Adaptive Least Significant Bit Matching Revisited Detection - Edris, Khalid Edris; Fakhreldin, Mohammed Adam Ibrahim; Jasni, Mohamad Zain; Tuty Asmawaty, Abdul Kadir (AENSI Publishing, 2014)
Spatial domain Steganalysis technology based on digital grayscale images has drawn a lot of interest in recent years. Edge Adaptive Least significant bit Matching Revisited(EALMR) steganography algorithm is high safety spatial domain information hiding technique which can choose embedding area based on the image context. In this paper, we propose Edge Adaptive Steganalysis algorithm based on histograms of the absolute difference of adjacent pixels to detect EALMR. The performance of the proposed steganalysis algorithm is evaluated and compared with five steganalysis algorithms. The results show that the proposed analytical algorithm based on histogram of absolute difference of adjacent pixels can effectively detect EALMR.